Apoyo en el desarrollo de actividades de ingeniería civil, en la constructora IPC Constructores S.A.S. - Diaz Lozano, Edwin Yamit (Universidad Antonio Nariño, 2023)
Currently the company IPC Constructores S.A.S. requires support for the management, design and execution of different projects, which are not carried out due to the lack of qualified personnel that said company does not have, these projects are linked to the following activities: 5 soil samples in the city of Duitama and its area of influence, which will be used to carry out soil studies, in the same way, the company has projected the construction of 4 cabins of 90 m^2 in the "La Parroquia" sector of the City of Duitama, in which it required the calculation of the quantities and budget of work. On the other hand, the company monitors previously carried out works and their guarantee, including a cabin with steep slopes that required slope stabilization. Additionally, the company made the quote and maintenance of a metallic structure. In works previously executed by the company, due to the lack of qualified personnel, there were failures in the execution of said projects, therefore, in this document, each of the support activities carried out by the intern in the planned projects and in execution using a mixed methodology that requires the characterization of said activities as well as their quantification in search of an improvement in the management of projects within the company